IMPACT OF AN INFECTION-CONTROL PROGRAM ON NURSES’ KNOWLEDGE AND ATTITUDE IN PEDIATRIC INTENSIVE CARE UNITS - Thamer Lafi Almutairi, Ahmed Furayhan Alshammari, Abdullah Malwah Al-Shammari, Suad Ridha Sulaiman Alshammari, Wafa Jaza Zahi Alshammari (Chelonian Research Foundation, 2022)
Healthcare-associated infections (HAIs) remain highly prevalent in pediatric intensive care units (PICUs), necessitating rigorous preventive programs. This concurrent embedded mixed methods study evaluated impacts of a multifaceted infection control program on nurse knowledge, attitudes, and practices in a 10-bed PICU in Hafar Al-Batin, Saudi Arabia. Quantitative data showed significant knowledge gains from a baseline mean score of 57% to 79% post-intervention, alongside increased perceived capacity and motivation to prevent HAIs. The HAI rate decreased from 13 to 9 per 1000 patient-days over six months. Qualitative analysis of three nurse focus groups revealed positive perceptions of the program’s multimodal education, reminders, feedback, leadership support, and motivational strategies. Suggested improvements included continued training, observational audits, and addressing environmental barriers. Integrated results provide a model to guide contextualized infection prevention programs in Saudi pediatric settings and beyond to achieve long-term gains in safety practices and outcomes. Keywords: infection prevention, pediatric intensive care, nurses, mixed methods evaluation, Saudi Arabia